High taxonomic resolution as a determinant on finding new species and new records in the Río de La Plata basin: a case on Chydoridae (Crustacea; Branchiopoda; Cladocera) - Debastiani Júnior, José Roberto [UNESP]; Elmoor-Loureiro, Lourdes Maria Abdu; Nogueira, Marcos Gomes [UNESP] (FapUNIFESP (SciELO), 2015)
Recent worldwide taxonomical research on Cladocera is discovering a number of new species but hardly in South America. The Río de La Plata is the second largest basin in the continent and the knowledge on cladocerans of the different sub-basins is uneven. The recent increase in the number of cladocerans species worldwide inspired this survey in the Río de La Plata basin. It was expected that new species, or at least a significant number of new records, could be found which would contribute to the richness of the least studied sub-basins. Twenty three sampling locations were selected and the Cladocera were analyzed in detail to the species level. The family Chydoridae was targeted due to its high species richness. Fifty species of Chydoridae were recorded, two of them probably new for science and a third one whose taxonomical status could not be further addressed, due to insufficient material for analysis. All sub-basins had at least one specimen of one or both new species. The contribution of new species was more homogeneous among subbasins when compared to the total contribution of new registers. It was concluded that the improvement of the taxonomical resolution and extensive samplings are fundamental in assessing the real cladoceran richness in the basin and that knowledge based on just a few research centers is not enough to promote secure taxonomical and biogeographical considerations yet.
Keywords: Phytophilous cladocerans; Geographical distribution; Taxonomy; Biogeography